Implementación del sistema de gestión de la seguridad y salud en el trabajo en “Coherco S.A.S”, basado en los lineamientos de los decretos 1072 del 2015, o52 del 2017 y la resolución 1111 del 2017 (2019)
Within Coherco SAS there wasn’t any document management system, or at least any idealized plan that could be evaluated. We have been carried out activities not only in safety and health at work parameters, but also in industrial engineering as it is the standard of the processes, the establishment of the procedures, the study of the functions and the necessary positions to be able to carry out the implementation of the management system.